Cooperation for a peaceful and sustainable world - Bo, Chen; Chatterji, Manas, 1937-; Na, Hou; Chaoyan, Hao (Emerald, 2013)
Over the last three decades, a considerable amount of work has been conducted in the field of peace studies, conflict management, peace science in economics, sociology, anthropology and management. This volume presents up-to-date, cutting-edge research by respected scholars with an emphasis on theoretical and mathematical constructs in the area of peace economics and peace science.
Keywords: Political Science -- General.; Political Science -- Political Freedom & Security -- International Security.; Political Science -- Peace.; Political science & theory.; Political economy.; Peace -- Economic aspects.; Peace-building -- Economic aspects.; Econometric models.; elektronické knihy; electronic books